Persepsi Risiko Dan Kepercayaan Pelanggan Dalam Mempengaruhi Loyalitas Pelanggan Terhadap Produk Elektronik Ramah Lingkungan - Samsul Arifin; Didit Darmawan; Jahroni Jahroni; Rafadi Khan Khayru; Utami Puji Lestari (CV. Aksara Global Akademia, 2023)
Today's industrial business competition causes manufacturers to pay attention to quality, price, and variety in developing new products to meet consumer needs. This research reviews the literature on green marketing and proposes a new conceptual framework on customer loyalty. It uses four constructs of perceived risk, customer trust, and customer loyalty. In environmentally friendly electronic products in Surabaya City. This study uses quantitative methods to prove the hypothesis. Data were obtained from 100 consumers who buy and use environmentally friendly electronic products, especially cell phones, computers, and laptops using purposive sampling method. The data were analyzed using multiple linear regression analysis. The results showed that risk perception and customer trust have a direct effect on customer loyalty